Financial Record Keeping and Financial Performance of Small and Medium-Sized Enterprises in Kampala District. - Mutesi Fatinah Mugabi (Uganda Christian University, 2023)
The study aimed at assessing the effect of financial record-keeping on the financial performance of small and medium enterprises among Kampala City traders. The study was guided by objectives, which included: establishing the effect of recording sales on the financial performance of SMEs; establishing the effect of entering vendor bills on the financial performance of SMEs; and establishing the effect of payroll management on the financial performance of SMEs. The research was carried out using both qualitative and quantitative survey research designs. Data was collected using questionnaires, and during the data collection, cluster random sampling was used. A sample size of 44 respondents was also used in the study. The major findings of the study indicated that sales recording played a crucial role in not only ensuring financial performance but also enabling effective financial management and decision making. The findings also revealed that efficient and accurate payroll management positively influenced SMEs’ financial performance in several ways, which included improved cash flow management, increased employee satisfaction and retention, enhanced compliance with regulations, and better overall financial stability. It also revealed that timely recording of vendor bills positively influenced the financial performance of SMEs in several ways. Lastly, a high correlation was determined between financial record-keeping and the financial performance of SMEs. The study recommended that there is a need for government authorities to bring in business experts who can offer more education and training to some of these business owners so that they can start recording their business transactions, improve their technological capabilities, especially with electronic record keeping, and get more professional training and education on how to effectively handle financial record keeping, among others.
This is a dissertation.